2001
DOI: 10.1021/ja011658v
|View full text |Cite
|
Sign up to set email alerts
|

The First 1,3-Disilabicyclo[1.1.0]butane with Long-Bridge Silicon−Silicon Bond

Abstract: The unique structures and reactivities of metallabicyclo[1.1.0]-butanes containing heavy main group elements have been the focus of experimental and theoretical studies. 1-3 As revealed by the theoretical calculations, one of the most interesting features of metallabicyclo[1.1.0]butanes 3 as well as bicyclo[1.1.0]butanes 4 should be the existence of the bond-stretch isomers, which differ primarily in the distance between the bridge head atoms. As shown in Chart 1, the short-bond (SB) isomers are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 25 publications
2
62
0
1
Order By: Relevance
“…Recently, Kira et al prepared the first 1,3-disilabicyclo-[1.1.0]butane, [1] a compound with a partially inverted SiÀSi bond. [2] A fully inverted SiÀSi bond is found in 1,3-disila-[1.1.1]propellane, a species that hitherto has not been made, even though the parent all-carbon [1.1.1]propellane and a pentastanna[1.1.1]propellane derivative, that is, ligand-stabilized cluster compounds with "naked" Group 14 atoms, [3] were prepared by Wiberg and Walker [4] and Sita et al [5] Of the larger synthesized [n.n.n]propellanes, only 3,7,10-trichalcogenaoctasila [3.3.3]propellanes [6] and a 1,6-disila- [4.4.4]propellane [7] have heavy Group 14 bridgehead atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kira et al prepared the first 1,3-disilabicyclo-[1.1.0]butane, [1] a compound with a partially inverted SiÀSi bond. [2] A fully inverted SiÀSi bond is found in 1,3-disila-[1.1.1]propellane, a species that hitherto has not been made, even though the parent all-carbon [1.1.1]propellane and a pentastanna[1.1.1]propellane derivative, that is, ligand-stabilized cluster compounds with "naked" Group 14 atoms, [3] were prepared by Wiberg and Walker [4] and Sita et al [5] Of the larger synthesized [n.n.n]propellanes, only 3,7,10-trichalcogenaoctasila [3.3.3]propellanes [6] and a 1,6-disila- [4.4.4]propellane [7] have heavy Group 14 bridgehead atoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the cases of 3 s-F and 3 s-Br , where the halogens can directly stabilize the silylenic center, this interaction is less pronounced (Scheme 1). Delocalization of Si"Si p electrons, through the divalent center, causes the observed disordered trend of the divalent angles \Si 2 Si 1 X [8,24]. Upon optimization, no rearrangement or ruptures are observed in silylenic species with structures 3 s-X and/or 3 tÀX (Fig.…”
Section: S-x And/or T-xmentioning
confidence: 93%
“…Consequently, attention has expanded to silicon-silicon double bonds and triple bonds containing silicon [16][17][18], as well as the small siliconcontaining rings [19]. More recently, Kira et al reported interesting examples of cyclic disilenes [20], spiropentasiladiene [21], 4-silatriafulvene [22], a silicon-containing fused bicyclic compound with a highly strained bridgehead double bond [23], and a disilane with a long Si-Si bridge [24]. Also, a stable silicon analogue of an allene, with a core of Si@Si@Si unit, with sp-hybridized silicon atoms, was synthesized [25].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Wiberg and co-workers generated a 5,6-dioxa-1,4-disilabicyclo[2.1.1]hexane having a Si,Si phantom bond of 2.309Å [14], and this is the record in short non-bonded Si,Si distances. The smallest disilabicyclic compound generated is the 1,3-disilabicyclo[1.1.0]butane of Kira and co-workers [15]. Interestingly, both of the last two compounds were stable until their melting points of 185 and 175-177 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%